Analyzing Current Challenges of School Leadership of Community Schools in Kathmandu Metropolitan City - Mainali, Bhawani Prasad (Tribhuvan University Journal, 2024)
School leadership initiates and influences the school community towards shared educational goals and fostering a positive teaching-learning environment there. This study aims to explore the current challenges faced by school leadership in the community schools. The data were collected from the head teachers, assistant head teachers and teachers from three community schools, three participants from each school by employing interview under interpretive epistemology. The data from the informants were transcribe, coded and the matisized. The reliability and validity were established by triangulation and multiple interviews. The result found that divergent challenges facing the community schools’ leadership such as excessive workloads, improper handling of rewards, socio-economic and diversity challenges of students, etc. Furthermore, the school leaders are required to focus on the strategies for addressing the current challenges such as, head teachers need more authority, staff equity, stakeholder meetings, legal reforms and staffing solutions. The study highlights the challenges faced by leaders in balancing administrative responsibilities and pedagogical leadership, affecting school performance and leadership practices. Community school leaders require professional development to improve the quality of education. It offers insights into strategies to improve leadership effectiveness and school outcomes. The result of the study would be beneficial to the leadership of community schools across Nepal.